Challenges and Prospects: Understanding Teachers' Attitudes towards the Teaching Profession in Ethiopia - Aklilu Alemu (Social Sciences and Humanities Open)
This study investigates Ethiopian secondary school teachers' attitudes towards their teaching profession, focusing on gender, education qualifications, and subject streams. It provides nuanced insights into the reasons behind negative attitudes, exploring societal attitudes, low salaries, and challenges faced by teachers. Using a cross-sectional design, 351 secondary school teachers in different regions completed a comprehensive questionnaire during their summer in-service training at an undisclosed university. Findings reveal that approximately half of the teachers exhibit negative attitudes, linked to societal attitudes and inadequate salaries. The study also examines the teachers' motivations for choosing the teaching career and reveals that most secondary school teachers joined the teaching profession because of a lack of alternative professions. The study also finds no statistically significant differences in attitudes by gender, education qualification, or subject stream. The study concludes that teachers fall short in student service delivery and strongly recommends that policymakers attract high-achieving individuals by offering competitive salaries, improving working conditions, and emphasizing the positive impact of teaching on societal development. Future research could employ qualitative methods to delve deeper into the underlying causes and nuanced situations influencing teachers’ perspectives on their profession in this, and other, low-income countries.